Two new species of Grandidierella (Amphipoda, Corophiida, Aoridea) from Singapore - Ali-Eimran, Alip; Lee, Yen-ling; Azman, B. A. Rahim (European Journal of Taxonomy, 2020)
Two new species of Grandidierella Coutière, 1904 from Singapore waters are described based on specimens collected during the Comprehensive Marine Biodiversity Survey (CMBS) between 2010–2015. Grandidierella pawaiensis sp. nov. differs from the rest in the genus by a combination of characters; (1) gnathopod 1 carpus proximoventral corner with apically acute process, (2) inner face of carpus of gnathopod 1 proximoventral corner with curved process, (3) proximal margin of dactylus of gnathopod 1 male with excavation, and (4) gnathopod 2 basis anterior margin crenulate. Grandidierella sungeicina sp. nov. on the other hand, is distinguishable from other related species of Grandidierella found in the tropical region by its paired mid-dorsal projections on pereonites 2 to 5, 1 ventrodistal triangular projection on pereonite 4, and gnathopod 2 ischium with 1 large trapezoid projection.